2018
DOI: 10.1002/ejoc.201800142
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Complexation of Chiral Oxirane Derivatives by an Enantiopure Cryptophane in Water

Abstract: We show here that optically active cryptophane 1 bearing phenol functions can efficiently bind the two enantiomers of 2‐(chloromethyl)oxirane, ethyloxirane, and 2,2′‐bioxirane derivatives in aqueous solution. The binding process is characterized by high‐field 1H NMR signals that are specific to the encapsulated species. In all cases, an enantioselective effect was observed and a relationship between the molecular volume of the guest and the binding constant can be established, even though the flexibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…91 On the other hand, dimethyloxirane does not show any affinity for host 47, whereas the two enantiomers of ethyloxirane can access the cavity of this host. 92 As observed, in the case of methyloxirane, different ECD spectra have been obtained in the 1 L b region with the two enantiomers of chloromethyloxirane.…”
Section: Binding Of Chiral Guests With Enantiopure Cryptophane Derivativesmentioning
confidence: 69%
See 3 more Smart Citations
“…91 On the other hand, dimethyloxirane does not show any affinity for host 47, whereas the two enantiomers of ethyloxirane can access the cavity of this host. 92 As observed, in the case of methyloxirane, different ECD spectra have been obtained in the 1 L b region with the two enantiomers of chloromethyloxirane.…”
Section: Binding Of Chiral Guests With Enantiopure Cryptophane Derivativesmentioning
confidence: 69%
“…Small chiral oxiranes derivatives such as methyloxirane (called also propylene oxide (PrO), V vdw = 57 Å 3 ), chloromethyloxirane (called also epichlorohydrin, V vdw = 72 Å 3 ), ethyloxirane (V vdw = 74.2 Å 3 ) and bis-oxirane (V vdw = 70.6 Å 3 ) are also well recognized by cryptophane derivatives bearing ethylenedioxy linkers. [90][91][92] For instance, it has been shown that the two enantiomers of methyloxirane fit well the cavity of anti-47 in basic aqueous solution. Thanks to the strong shielding effect of the benzene rings surrounding the guest molecule, the proton signals in the 1 H NMR spectrum of the encapsulated guest are observed at lower frequencies than those of the free guest in solution.…”
Section: Binding Of Chiral Guests With Enantiopure Cryptophane Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…The propagation of the chirality along linkers and even to the opposite face of the cage could lead to highly efficient enantioselective sensors, due to the presence of a strongly controlled chiral environment around the guest-binding site. Indeed, although examples of C 3 -symmetrical cages displaying enantioselectivity in the recognition of chiral guests remain rare (Sambasivan et al, 2010 ; De Rycke et al, 2018 ), it has been recently shown that remarkable enantioselective recognition of chiral neurotransmitters or carbohydrates can be reached by hemicryptophane cages presenting a C 3 symmetrical axis (Long et al, 2018b ; Yang et al, 2020 ). Secondly, by controlling the chirality at both first and second coordination sphere levels of metal complexes, promising chiral confined catalysts for enantioselective transformations could be obtained.…”
Section: Conclusion Discussion and Future Directionsmentioning
confidence: 99%